Search for the Nile's Source : the ruined reputation of John Petherick, nineteenth-century Welsh Explorer. - Humphries, John (University of Wales Press, 2013)
In this book, John Humphries questions whether John Petherick was a slave trader or a victim of conspiracy on the Nile.